The grease of the wheel: The correlation between corruption, regional revenue and expenditure in Indonesia - Sanda Aditiya Arsandi (Integritas: Jurnal Antikorupsi, 2022)
Previous research has revealed that corruption is considered to have two types of effects on the economy. Corruption is seen as an obstacle to the economy but also as a "grease of the wheel" that accelerates the rotation of economic cogs. This study aims to determine the position of corruption in Indonesia after fiscal decentralization. The study was conducted based on secondary data obtained from the publications of the Central Statistics Agency and the Corruption Eradication Commission. The test was carried out using correlation analysis from 2006-2020 to see the effect of corruption in the regions and private sector on its economic dimension. Results show that corruption in the regions has a significant positive effect on corruption in the private sector and the realisation of regional revenue and expenditure. These results support the argument that in Indonesia, the phenomenon of corruption as a grease of the wheel still occurs.